Analisis Strategi Pembelajaran Aqidah - Muhammad Ilham Syahputra (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2021)
The learning strategy is the teacher's perspective and mindset in teaching. In developing learning strategies, at least the teacher must consider several things, including: how to activate students, how students build concept maps, how to collect information with effective question stimulus, how to extract information from print media. Learning forms a strategy, because learning strategy is a learning activity that must be carried out by teachers and students so that the objectives of learning activities can be achieved effectively and efficiently. Another opinion also states that the learning strategy is a set of learning materials and procedures that are used together to produce learning outcomes for students. Aqidah is one of the Islamic religious subjects that is used as a source of law to achieve outward progress and spiritual happiness. Aqidah lessons are the scope of Islamic religious education, namely conscious and planned efforts in preparing students to recognize, understand, appreciate and believe in Allah and realize it in noble moral behavior in everyday life through guidance, teaching, training, and use of experience.